Savvy - Law, Ingrid, 1970- (New York, N.Y., U.S.A. : Puffin ; Burlington, MA : Walden Media, 2010)
Recounts the adventures of Mibs Beaumont, whose thirteenth birthday has revealed her "savvy"--a magical power unique to each member of her family--just as her father is injured in a terrible accident.
Includes preview of Scumble, "the next book about the Beaumont family".
"First published in the United States of America by Dial Books for Young Readers ... 2008"--T.p. verso.
Accelerated Reader AR
Rebecca Caudill Nominee, 2011.
Keywords: Magic -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Magic -- Fiction; Brothers and sisters -- Fiction; Voyages and travels -- Fiction